American Grand Strategy: Obama's Middle East Legacy - Özdemir, Çağatay. author. (orcid)0000-0001-9477-9761 Link aut Link
XIII, 214 p. 2 illus.
Keywords: This book provides a comprehensive analysis of American grand strategy during the Obama administration and its impact on the Middle East. It explores the concept of grand strategy, examining how national objectives and security priorities influence foreign policy decisions. The text compares Obama’s approach to those of his predecessors, Bill Clinton and George W. Bush, highlighting key decisions and their consequences. The book focuses especially on issues such as the conflicts in Afghanistan and Iraq, the Arab uprisings, nuclear negotiations with Iran, and the Israel-Palestine conflict. The book also examines the long-term effects of Obama’s policies on U.S. foreign relations, offering insights into the successes and challenges faced in the Middle East. Lastly, it considers the evolution of the American grand strategy under the subsequent administrations of Trump and Biden, shedding light on the continuity and shifts in America's foreign policy direction. This work is essential for anyone interested in U.S. foreign policy, Middle East politics, and grand strategy. Çağatay Özdemir completed his doctorate at Marmara University and became an Associate Professor in International Relations, specializing in America, the Middle East, and Transatlantic Studies. He authored The Rise and Fall of the Eagle: An Assessment of the Liberal World Order and Türkiye's Soft Power Re-Imagined on Its Centennial.